1990
DOI: 10.1210/endo-126-3-1435
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-β Modulation of Prolactin Secretion from Rat Anterior Pituitary Cells: Involvement of Adenylate Cyclase Activity and Calcium Mobilization*

Abstract: Recent findings indicate that interleukin-1 beta (IL1 beta), a monokine secreted by stimulated macrophages and monocytes, modulates neuroendocrine functions in a manner similar to classical hormones. In this study we show that IL1 modulates PRL secretion, assessed by reverse hemolytic plaque assay, and describe the effect of the monokine on adenylate cyclase activity and calcium fluxes in rat normal pituitary cells. In basal and vasoactive intestinal peptide (VIP)-stimulated conditions, low doses of IL1 reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…This is supported by a study in rats which showed that IL1b was able to inhibit prolactin release. 32 However, inhibitory as well as stimulatory effects of cytokines on prolactin release have been described, and future research will be needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a study in rats which showed that IL1b was able to inhibit prolactin release. 32 However, inhibitory as well as stimulatory effects of cytokines on prolactin release have been described, and future research will be needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 whose receptor was detected within mouse adenohypophysis [104], inhibits prolactin (PRL) secretion from dispersed rat pituitary cells through the regulation of both cAMP production and agonist-induced Ca ++ fluxes [105][106][107]. IL-1 mRNA was identified in rat anterior pituitary cells supporting an autocrine/paracrine regulation of pituitary function in situations in which stimulation of IL-1 secretion is induced, such as during infectious processes [108].…”
Section: Autocrine/paracrine Functions Of Chemokine In Normal Pituitarymentioning
confidence: 98%
“…In particular, it was reported that interleukin 1 b (IL-1b), that is produced by hypothalamic neurons (Johnson et al 2004) inhibit prolactin secretion from dispersed rat pituitary cells through the regulation of both cAMP production and agonist-induced Ca CC fluxes (Schettini et al 1990). Indeed, the expression of its receptors was detected within the mouse adenohypophysis (Cunningham et al 1992).…”
Section: Chemokine Modulation Of Normal Pituitary Functionmentioning
confidence: 99%